Altruism and beyond an economic analysis of transfers and exchanges within families and groups - Stark, Oded (Oscar Morgenstern memorial lectures, 1995)
Finally, altruism, which in the beginning of the book is assumed, is explained: the transmission to or probable acquisition by children of parental traits and the exchange between siblings are shown to result in a stable equilibrium wherein no agent behaves nonaltruistically. The book studies both altruistic and nonaltruistic motives for transfer behavior. In addition, it traces some of the market repercussions of intrafamilial, intergenerational, and intragroup transfers and exchanges